Microstructure and corrosion resistance manipulation of directed energy deposited Cu–Al alloys with varied Al contents - Changliang Yao; Shanshan He; Ki-Yong Lee; Do-Sik Shim; Kwang-Yong Shin (Journal of Materials Research and Technology)
Cu–Al alloys are widely utilized in the electrical, aerospace, and automotive industries. In this study, Cu–Al alloys with varying Al contents (ranging from 6, 8, 10, 12, and 14 wt%) were fabricated by directed energy deposition (DED) using two types of powders: CuNi2SiCr and Al–Mg-0.7Si. The deposition sample with 14 wt% Al fractured due to the high γ2 phase content while the others exhibited good quality, without cracks or significant defects. The 6 wt% Al exhibited a typical DED melt pool microstructure, which is composed of a single α phase. As the Al mass fraction increased, the microstructure became finer, and disordered (β′) and ordered (β1) needle-like martensite appeared in 8, 10, and 12 wt% Al samples. Furthermore, a β→(α+γ2) eutectoid transformation occurred at high Al content, resulting in the appearance of plum blossom-shaped γ2 phase in 10 and 12 wt% Al samples. The properties and oxide film formation on each sample were investigated using electrochemical measurements. The corrosion resistance of the samples increased with increasing Al content. Moreover, the 12 wt% Al sample exhibited the smallest corrosion rate, with corrosion resistance comparable to cast NAB, which is attributed to the protection of the dense Al2O3 oxide film that formed on its surface. Furthermore, the formation mechanism of the oxide film and the corrosion behavior of the microstructure of each specimen were discussed in detail through long-term immersion corrosion tests. This study provides effective strategies and new ideas for constructing Cu–Al alloys with excellent corrosion resistance.